PENGARUH ISENTIF DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN PEMAHAMAN PERPAJAKAN SEBAGAI VARIABEL MODERASI - Lestari, Puji (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The objectives to be achieved in this research are to review and analyze the effect of tax incentives on MSME Taxpayer compliance, to review and analyze the effect of tax sanctions on MSME Taxpayer compliance, to review and analyze the effect of understanding taxation can moderate tax incentives on MSME Taxpayer compliance, as well as to review and analyze the effect of understanding taxation can moderate tax sanctions on taxpayer compliance MSMEs. The type of research used in this study is research with a quantifiable method in a descriptive form. The research method used is the causal method (causal explanatory). The population in this study is individual taxpayers and MSME actors in the Tangerang City Prohibition District area, which is 1,590 taxpayers. The results obtained from the research that has been carried out, Tax Incentives have a significant positive effect on MSME Taxpayer compliance, Tax Sanctions have a significant positive effect on MSME Taxpayer compliance, Tax Incentives on Taxpayer Compliance with Moderated by Tax Understanding have a significant positive effect on MSME Taxpayer Compliance and Tax Sanctions on Taxpayer Compliance moderated by Tax Understanding have a significant positive effect on MSME taxpayer compliance in the Tangerang City Prohibition District Area.